Numerical Analysis of Poro-elastic Materials Described by the Micro-dilatation Theory. (2017) - Repka, Miroslav; Sládek, Vladimír; Sládek, Ján
Abstract: Numerical computational techniques can be conveniently utilized for the analysis of porous structural materials with vacuous pores. The presence of voids or pores in these materials affects their material properties and overall performance therefore it is of great importance to study the structural integrity of such materials. The micro-dilatation theory firstly developed by Cowin-Nunziato (C-N) has been applied in this study to describe the porous materials with vacuous pores. This theory belongs to the general continuum theories and uses linear elastic theory with additional kinematic variable called porosity change function. Thus, the deformation and porosity are coupled fields giving the response of the body under external loads. However in spite of the number of papers concerning the numerical analysis of C-N theory, this theory still remains unresolved and physically unclear. It is the aim of this paper to provide some numerical examples in order to contribute to better understanding of the theory. The derived FEM formulation has been developed and incorporated into the commercial software COMSOL via weak form module. The numerical studies are verified with analytical solution.